Proses Produksi Mixer Tank Kapasitas 500 Liter Pada Pt. Xyz - Sacarya Linggi Allo; Rizal Hanifi; Ratna Dewi Anjani (Jurnal Ilmiah Wahana Pendidikan, 2022)
Mixer tank is used to homogenize a fluid and prevent deposition in the fluid. The material in the main components of the tank, namely the main tank and agitator, uses 316L stainless steel while supporting components such as frames and accessories use stainless steel 304. The production process is carried out in the Workshop Department area, components are manufactured based on the design that has been made by the engineering / drafter. Machines used in the production process include rolling machine, hydraulic shear machine, hydraulic pressbrake machine, turning machine, milling machine, metalex fabrication equipment (or commonly called coak machine), welding machine, grinding machine and plasma cutting. The final result of the design and production process is a 500 liter capacity mixer tank